2021
DOI: 10.1049/ntw2.12017
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing topic clustering for Arabic security news based on k‐means and topic modelling

Abstract: The internet has become one of the main sources of news spread as it unleashed the information dissemination space, where the news websites express opinions on entities while also reporting on recent or unusual security risks. Recently, many research studies have focused on sentimental reflection on the views and impressions of people utilising natural language processing and analytical linguistics. Therefore, we have collected corpus from popular Arabic websites that publish articles related to recent securit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…Static analysis methods, which extract key features from code for input into machine learning models, have been a focal point of some studies (Kim et al, 2022;Li et al, 2016. In contrast, others have utilized dynamic analysis, where the code is executed, and its behavior monitored to identify vulnerabilities (Alharbi, Hijji & Aljaedi, 2021;Salimi & Kharrazi, 2022).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Static analysis methods, which extract key features from code for input into machine learning models, have been a focal point of some studies (Kim et al, 2022;Li et al, 2016. In contrast, others have utilized dynamic analysis, where the code is executed, and its behavior monitored to identify vulnerabilities (Alharbi, Hijji & Aljaedi, 2021;Salimi & Kharrazi, 2022).…”
Section: Related Workmentioning
confidence: 99%
“…Deep learning architectures such as Convolutional Neural Networks (CNNs) and RNNs have been extensively studied for vulnerability detection (Alharbi, Hijji & Aljaedi, 2021;Kim, Woo, Lee & Oh, 2017;Kim et al, 2022;Li et al, 2016;Rabheru, Hanif & Maffeis, 2021;Salimi & Kharrazi, 2022;Yamaguchi, Golde, Arp & Rieck, 2014;Zhou & Verma, 2022). These models typically require structured data for identifying features linked to vulnerabilities.…”
Section: Related Workmentioning
confidence: 99%
“…Myriad studies have unveiled methodologies that employ machine learning techniques for this pursuit. Some concentrate on static analysis, extracting salient features from the code to be input into predictive machine-learning frameworks [1,2], while others hinge on dynamic analysis, running the code and monitoring its behavior to discern vulnerabilities [3,4]. A nascent inclination towards harnessing deep learning models for source code vulnerability detection has been observed.…”
Section: Related Workmentioning
confidence: 99%
“…Meanwhile, other investigations employ transformers, which have gained acclaim in the realm of natural language processing [9,10]. Literature has extensively analyzed deep learning architectures like Convolutional Neural Networks (CNNs) and Recurrent Neural Networks (RNNs) for vulnerability detection [3,[12][13][14]25,29,31,34]. Yet, these models necessitate structured data to discern vulnerability-associated features.…”
Section: Related Workmentioning
confidence: 99%
“…Finally, it is worth highlighting that a series of studies has considered the presence of topics over time. These studies identified and evaluated expert opinions on COVID -19 [72] during the outbreak period compared with other periods [73].…”
Section: ) Root (Classics)mentioning
confidence: 99%